PENINGKATAN PENGETAHUAN DAN SIKAP REMAJA TERHADAP NARKOBA MELALUI KEGIATAN PENYULUHAN DI SEKOLAH MENENGAH UMUM - Murtaqib, Murtaqib; Rahmawati, Iis; Sulistiyorini, Lantin (IKESMA, 2007)
Drug abuses as a social phenomenon in Indonesia especially in big cities just started and seem to be focus everywhere in this country in 1969. However, year by year, drug abuse was increasing especially in big cities in Indonesia which apparently with different patterns, which turns out, lately has attacked school-age group (from 6 to 21 years old). It is such an irony; they actually are the generations on whom we expect to continue of the admirable life of our nation.This research was aimed at gaining a description on whether or not the health education about drugs affected to the knowledge and the attitude of juveniles toward drugs. The sample in this research was the second group of the third grade students of social science. The method in this research was experimental with pre-post test one group design. The sampling technique used was purposive sampling. The data were collected by questionnaire. The result of this research revealed that there was an improvement in the respondens knowledge and attitude toward drugs. Those who lacked of knowledge on drugs became quite knowledgeable after health education. Their attitude was also improving. Before the health education, they had average attitude toward drug and became goods attitude after health education. Conclusion, health education had significantly affected to the juvenileâs knowledge and attitude toward drugs.Â Keywords : health education, attitude, knowledge, drugs